Impact of Mahatma Gandhi National Rural Employment Guarantee Act (MNREGA) on the Livelihood Security of the Beneficiaries in West Bengal - Roy, Shubhadeep; Singh, Baldeo; Padaria, R.N. (Indian Journal of Extension Education, 2012)
The study was conducted in two districts namely, Burdwan and South Dinajpur of West Bengal, with 200 MNREGA beneficiaries as respondents to assess the impact of MNREGA on their livelihood security. Significant changes were found in food security, income security, habitat, health and environmental security of the respondents after working under MNREGA. Majority of the respondents (82.5%) were found under medium livelihood security category. Whereas 80.5 per cent of the respondents were found under low livelihood security category before implementation of MNREGA. The Study showed that a majority of the respondents shifted from low to medium livelihood security category after commencement of MNREGAin the study area.
Keywords: Livelihood security; Food security; Income security; Habitat security; Educational security; Health security; Social security; Environmental security